Оцінка процесу розробки моделі програмної системи методами теорії автоматів та мереж Петрі - Пархоменко, Б. Є. (ХНУРЕ, 2024)
The thesis is devoted to the analysis and research of the process of developing software systems using the theory of automata and Petri nets. The study includes an analysis of existing software development techniques and their adaptation for use in the context of automata theory and Petri nets. In particular, the thesis examines the effectiveness of the application of the theory of automata and Petri nets for modeling, analysis and verification of software systems. Special attention is paid to the methods of formalization and mathematical apparatus used to describe the processes of development of software systems.
Keywords: мережа Петрі